2016
DOI: 10.1038/gim.2015.181
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of genetic information on children: a systematic review

Abstract: Purpose: This review assessed the psychological impact that acquiring personal and familial genetic information has on children. We also examined the concordance between the available empirical data and clinical guidance/perspectives articles. Methods:We screened 591 abstracts and identified 13 studies, representing 966 children. Ten studies assessed 386 children tested for familial adenomatous polyposis (n = 171), hereditary cardiac disease (n = 134), and other conditions (n = 81). Three studies addressed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 57 publications
4
96
0
Order By: Relevance
“…Despite concerns about potentially exacerbating parental and patient anxiety, genetic counseling has been found to allay fears and to empower families by providing fact-based risk information and potential options for proactive risk reduction and/or early detection strategies if a gene mutation is identified (29,30).…”
Section: Pretest Genetic Counseling and Informed Consentmentioning
confidence: 99%
“…Despite concerns about potentially exacerbating parental and patient anxiety, genetic counseling has been found to allay fears and to empower families by providing fact-based risk information and potential options for proactive risk reduction and/or early detection strategies if a gene mutation is identified (29,30).…”
Section: Pretest Genetic Counseling and Informed Consentmentioning
confidence: 99%
“…Finally, previous research has highlighted the psychological implications for children acquiring genetic information, 11 and short-term assessment reveals few adverse reactions. 15,29 However, considering the dearth of new types of genetic testing, further longitudinal studies are required in children to explore the benefits and ramifications of acquiring genetic information at various points before and after testing is conducted.…”
Section: 141828mentioning
confidence: 99%
“…9,10 As such, it is prudent to remain skeptical about offering genetic testing to identify survivors' risk of developing late effects until more data is available. 11 The potential psychological impacts, along with concerns regarding family planning, fertility, lifestyle choices and health management, 5,12 indicate individualized management and genetic counseling should remain a priority. 3,10 A large body of research has investigated public [13][14][15][16][17] and patient 1,3,[18][19][20][21][22] perceptions of genetic testing, and reported that despite low levels of understanding, perceived benefits outweigh the risks.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This latter issue is amenable to empirical investigation and although relatively under-researched, two recent systematic reviews have assessed the available evidence. 6,7 These early data, largely confined to effects of testing for carrier status or predicting single gene disorders, suggest that serious impacts on traditional psychological parameters such as anxiety and depression are uncommon. However, both reviews highlighted the constrained nature of the data and significant methodological limitations of many studies.…”
Section: Introductionmentioning
confidence: 99%
“…These effects may include potential disruptions to children's developing identities, and complex family or social impacts that might initially be best explored using mixed methods approaches. 6,7 The study reported here aims to begin to address some of these issues in the context of genomic NBS, by providing 12-year follow-up data for a cohort of children tested at birth for genetic susceptibility to a single condition, type 1 diabetes (T1D). T1D represents a useful disease model, both for studying the complex genetic and environmental interactions underlying multifactorial disease development and for investigating psychological reaction to newborn testing.…”
Section: Introductionmentioning
confidence: 99%